Persepsi Remaja Aktif Media Sosial Terhadap Peran Spiritualitas Dalam Menghadapi Tekanan Psikologis - Neneng Nurhasanah; Gina Kania; Hasan Al Banna; Riki Faisal; Irena Laras (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The digital era has brought significant changes to the lives of adolescents, particularly through the intensity of social media use, which impacts their psychological well-being. Social pressure, anxiety, and feelings of inadequacy are common phenomena arising from these online activities. In this context, spirituality is seen as a potential inner strength capable of supporting adolescents' psychological resilience. This study aims to describe the perceptions of adolescents active on social media regarding the role of spirituality in coping with psychological distress. The study used a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation at Madrasah Aliyah Al Huda, Tegalwaru District. The results show that most adolescents view spirituality as important, but it is still limited to formal religious practices such as prayer and Quran recitation. The role of spirituality as a mental strengthening tool has not been fully internalized in daily life, although some students reported feeling emotional calm through certain religious activities. The madrasah environment supports religious activities, but has not systematically directed spiritual development as a strategy for coping with psychological distress. These findings have important implications for the development of spiritual education programs that are more applicable and relevant to digital challenges. This research also opens up space for further study on the integration of spiritual and psychological development in religious education environments.